Mesogenic origami – four-armed, star-shaped mesogens as precursors for functional liquid crystal materials. Issue 12 (21st October 2017) - Roth, S.; Lehmann, M.
ABSTRACT: A series of symmetrical tetraesters with a tetrahydroxybenzene core, semi-flexible oligobenzoate arms and one to three peripheral aliphatic chains per arm have been synthesised to study the influence of space-filling and nanosegregation in the mesophases. All compounds were comprehensively investigated by polarised optical microscopy, differential scanning calorimetry and X-ray scattering techniques. Modelling based on this data revealed that the competition of space-filling and nanosegregation furnishes a number of columnar and lamellar phases. Various folded molecular structures are the basic mesogenic building blocks. In contrast to earlier predictions, the tetraesters fold to lath-, cross-, cone- and bowl-like conformers depending on the type of the mesophase. Graphical Abstract: